Family Problems in Budi Wahyono's Short Stories and Their Relevance to Real Life - Fajrin Dwi Artika; Harjito Harjito; Senowarsito Senowarsito; Nazla Maharani Umaya (Green Publisher Indonesia, 2025)
This research examines family disorganization in contemporary Indonesian society through the literary lens of Budi Wahyono's short story collection, Tak Ada Sejengkal Tanah untuk Sajadah. Employing a qualitative descriptive method with a sociological approach, the study analyzes ten stories to identify prevalent family issues and their correlation with social reality. The findings reveal that communication breakdown is the predominant cause of family disorganization, appearing in 80% of the narratives. Other significant factors include shifting gender roles, infidelity, divorce, psychological disorders, economic disparities, and conflicting life perspectives. The literary depictions demonstrate a strong correspondence with actual family dynamics in Indonesia, validating literature's role as a mirror of social phenomena. The writer's background shapes the narratives, creating thematic consistency and authentic portrayals of common family conflicts. This research contributes to literary sociology by showing how fictional narratives can accurately reflect social realities. It also offers practical value for educators seeking to use literature as teaching material for understanding complex family dynamics. Furthermore, it lays a foundation for interdisciplinary research that integrates literary analysis with family counseling and social work practices, highlighting culture-specific insights into Indonesian family challenges.